Jurisprudence Issues that Imam Tirmidhi Attributed in his Sunnah to the People of Kufa or Some of them - Collection, Documentation and Study - (Chapters of Prayer) - Majeed , Mohammed (Islamic Sciences Journal, 2023)
Sunan Al-Tirmidhi for the compilations of hadith that Imam Al-Hafiz Abu Issa Muhammad bin Isa bin Surah bin Musa bin Al-Dahhak Al-Tirmidhi have authored, Who was called Tirmidhi in reference to the ancient city of Tirmid, which is located on the edge of the Balkh River, Imam Al-Tirmidhi, may Allah Almighty have mercy on him, has mentioned in his work a number of jurisprudential opinions and attributed them to the people of Kufa, This is because of the scientific importance of Kufa to Muslims, until a special school of jurisprudence has been recorded by their name, It is the product of the students of its jurisprudence by the great companion Abdullah bin Masoud and other companions, may Allah be pleased with them. Among the most prominent of its men was Imam Abu Hanifa, may Allah Almighty have mercy on him and his companions, Allah have employed them for the sake of this religion. They have exerted themselves in order to protect this religion, defend it and call for it, From the time of the Companions to the present day, and Due to the importance of this work and its contents, I collected what Imam Al-Tirmidhi has said about the people of Kufa in the chapter on prayer and studied it critically, with documentation and weighting.